Encyclopedia of Life Sciences 2020
DOI: 10.1002/9780470015902.a0028894
|View full text |Cite
|
Sign up to set email alerts
|

Plant Phenotyping

Abstract: Every plant science experiment starts with a design that will be adapted to answer a specific biological question and involves evaluation of phenotypic traits. Plant phenotyping has advanced from manual measurements of physiologically relevant parameters to high‐throughput phenotyping platforms that use robotics and imaging sensors. Yet, this game‐changing technology has its own challenges, namely data analysis and interpretation. The improved quality of the sensors used in the phenotying experiment provides i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 78 publications
0
19
0
Order By: Relevance
“…More recently, salinity studies have begun investigating new traits that can potentially contribute to salinity tolerance (Morton et al ., 2019; Negrão et al ., 2017; Zelm et al ., 2020), including stress signalling pathways (Choi et al ., 2014; Evans et al ., 2016), cell wall remodelling (Feng et al ., 2018), transpiration‐use efficiency (Al‐Tamimi et al ., 2016) and root system architecture (Julkowska et al ., 2017), thus breaking down salinity tolerance into more genetically tractable components (Morton et al ., 2019). The non‐destructive methods developed in high‐throughput phenotyping allowed the recording of more sophisticated traits (Awlia et al ., 2016), providing the simultaneous and multifaceted understanding of plant size, architecture and photosynthetic efficiency during plant development and in response to environmental cues (Negrão and Julkowska, 2020). In this study, the focus was on exploring the natural variation in the early responses to salt stress by applying high‐throughput phenotyping protocols and GWAS on the Arabidopsis thaliana mapping population.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, salinity studies have begun investigating new traits that can potentially contribute to salinity tolerance (Morton et al ., 2019; Negrão et al ., 2017; Zelm et al ., 2020), including stress signalling pathways (Choi et al ., 2014; Evans et al ., 2016), cell wall remodelling (Feng et al ., 2018), transpiration‐use efficiency (Al‐Tamimi et al ., 2016) and root system architecture (Julkowska et al ., 2017), thus breaking down salinity tolerance into more genetically tractable components (Morton et al ., 2019). The non‐destructive methods developed in high‐throughput phenotyping allowed the recording of more sophisticated traits (Awlia et al ., 2016), providing the simultaneous and multifaceted understanding of plant size, architecture and photosynthetic efficiency during plant development and in response to environmental cues (Negrão and Julkowska, 2020). In this study, the focus was on exploring the natural variation in the early responses to salt stress by applying high‐throughput phenotyping protocols and GWAS on the Arabidopsis thaliana mapping population.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, salinity studies have begun investigating new traits that can potentially contribute to salinity tolerance (Negrao et al, 2017, Morton et al, 2019, van Zelm et al, 2020, including stress signaling pathways (Choi et al, 2014;Evans et al, 2016), cell wall remodeling (Feng et al, 2018), transpiration use efficiency (Al-Tamimi et al, 2016) and root system architecture (Julkowska et al, 2017), thus, breaking down salinity tolerance into more genetically tractable components (Morton et al, 2019). The non-destructive methods developed in highthroughput phenotyping allowed the recording of more sophisticated traits (Awlia et al, 2016), providing simultaneous and multifaceted understanding of plant size, architecture and photosynthetic efficiency during plant development and in response to environmental cues (Negrão and Julkowska, 2020). In this study, we used high-throughput phenotyping to enable indepth GWAS and have identified over 1,000 unique SNPs that were associated with the responses of Arabidopsis to salt stress ( Table S3, Table S4).…”
Section: Discussionmentioning
confidence: 99%
“…royalsocietypublishing.org/journal/rsob Open Biol. 12: 210353 measurement of traits such as shoot and root length, fresh and dry mass as well as yield components such as number of productive tillers or branches, fruit or grain weight etc [7,18]. Destructive phenotyping entails no highly specialized nor expensive equipment.…”
Section: Phenotyping Technologies To Assess Abiotic Stressesmentioning
confidence: 99%
“…Breeders heavily rely on phenotyping, using large number of genotypes and targeting the collective study of multiple traits simultaneously under a given condition. The challenge rests on breeding for yield and other traits, such as stress tolerance, using the most adequate phenotyping strategy for the trait of interest among a plethora of available phenotyping strategies (as reviewed by [18,71]). High-throughput phenotyping (HTP) aims to characterize the full set of phenotypes by non-destructively, capturing plant traits and integrating biology with computers and robotics (as reviewed by [15,72,73]).…”
Section: High-throughput Phenotypingmentioning
confidence: 99%
See 1 more Smart Citation